PENGARUH PENGALAMAN, BIAYA OPERASIONAL DAN HASIL TANGKAPAN TERHADAP PENDAPATAN NELAYAN PURSE SEINE DI DESA PEJALA PAGATAN KECAMATAN KUSAN HILIR KABUPATEN TANAH BUMBU - Shaleha Shaleha; Khairi Pahlevi (PPJP Universitas Lambung Mangkurat, 2020)
This research was conducted in the village Pejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District with the aim of knowing (1) to find out whether the experience, operational costs, and catch results factors together affect the income of Purse Seine fishermen in the village Pejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District ; (2) to find out what factors most influence the income of Purse Seine fishermen in the village Pejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District. Respondents in this study were 20 fishermen in the village of Purse Seine fishermen in the village Pejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District. Data is processed using multiple regression analysis, hypothesis testing and classical assimilation tests.The results showed that jointly the experience, operational costs and Catches effect on income of purse seine fishermen in the village of Purse Seine fishermen in the village Pejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District. The Catches variable (X3) is the factor that most influences the income of the village of Purse Seine fishermen in the village Pejala Pagatan, Kusan Hilir Subdistrict, Tanah Bumbu District.Keywords : Experience, Operational Costs, and Catches.